Developments in conducting polymer fibres: from established spinning methods toward advanced applications. Issue 50 (9th May 2016) - Mirabedini, Azadeh; Foroughi, Javad; Wallace, Gordon G.
Abstract : This review provides a comprehensive picture of the history and latest developments in the field of conducting polymer fibres as well as their current/future applications. Abstract : Conducting polymers have received increasing attention in both fundamental research and various fields of application in recent decades, ranging in use from biomaterials to renewable energy storage devices. Processing of conducting polymers into fibrillar structures through spinning has provided some unique capabilities to their final applications. Compared with non fibrillar forms, conducting polymer fibres are expected to display improved properties arising mainly from their low dimensions, well-oriented polymer chains, light weight and large surface area to volume ratio. Spinning methods have been employed effectively to produce technological conducting fibres from nanoscale to hundreds of micrometre sizes with controlled properties. This review considers the history, categories, the latest research and development, pristine and composite conducting polymer fibres and current/future applications of them while focus on spinning methods related to conducting polymer fibres.